Estudio de prefactibilidad para la instalación de una planta procesadora de fideos enriquecidos con maca - Honderman Ubillus, Diego Alexis (2020)
The current thesis stands for the development of the implementation of a plant of pasta enriched with maca to satisfy a determined demand in Peru. Through thirteen chapters, it is reviewed many topics that support the hypothesis of the viability of a business creation dedicated to production and selling of pasta enriched with maca for a period of five years which corresponds to the project's life. In the first chapter called general aspects, it is indicated the reasons and objectives of the current project. Besides, the hypothesis and frames which limit the thesis' scope are stablished. In the next chapter, the study illustrates all related to the business research. Being the most highlighted the market segmentation and calculating of the market share to satisfy. The following chapter named plant's localization allows us to identify both macro and micro level, the most suitable place to install the factory, based on multiple factors. In the successive chapter plant's size, it is decided the magnitude that the factory should have, based on the most suitable element among the factors market, productive resources, technology and breakeven. The fifth chapter analyzes the related to the project's engineer talking about different subjects. It starts with the analysis and selection of the most appropriate technology for the size of the plant chosen. Also, it is explained to the detail the production process and its characteristics, the calculation of matter's flow in the processes and the capacity installed. As well, it is stablished the components to take into account for the protection of the quality, environment, security and health and machinery, according to the Peruvian and international law. Additionally, it is calculated the supply requirement, services and indirect personal and, furthermore, it is calculated the size and distribution of the plant. Keeping with the structure, the sixth chapter describes the organization's composition such as job positions and self-configuration. In the ensuing chapter called budget and assessment, the expenses and costs that are part of the investment are backed up. In addition, it is presented the financial reports and theirs respective assessments that confirm the economic and financial feasibility, with VNA positive and TIR above COK. The adjacent chapter social assessment shows the benefits and costs of the project, from the social well-being perspective.